Bangladesh computer and software engineering tertiary education in 2018 tracer study. (Metro Manila, Philippines Asian Development Bank, 2019)
It also assesses the accessibility, quality, and relevance of computer and software engineering university programs and identifies possible areas for improvement. The study provides useful evidence for policy interventions to enhance the countrys information technology and information technology enabled services industry, a key priority for the government under its Digital Bangladesh initiative.
Keywords: Educational innovations; Technical education; Electronic books